Incidence of dysmenorrhoea associated with high stress scores among the undergraduate Nepalese medical students - Pramanik, T; Shrestha, R; Sherpa, MT; Adhikari, P (Journal of Institute of Medicine Nepal, 2011)
Introduction: Primary dysmenorrhoea is one of the major problems associated with menstruation among the young undergraduate medical students which affect their daily routine. Among various causes, mental stress is one of the major causes of primary dysmenorrhoea. This study aims to assess the relationship between the degree of stress and incidence of dysmenorrhoea amongst the young Nepalese medical students. Methods: Young, unmarried, non-smoker female medical undergraduate students (age: 18-20years, n = 104) having no pelvic pathology participated in this study. A baseline questionnaire was used to note the medical history on menstruation, use of contraceptive pills, active or passive smoking exposure and alcohol use. The independent and individual perception of stress was evaluated by using a stress questionnaire. Results: Result indicated that the stress score is significantly higher (31.30 vs. 18.81) in dysmenorrhoeic women (n=50) compared to eumenorrhoeic participants (n=54). Conclusions: The present study indicated a positive relationship between psychological stress (supported by stress scores) and dysmenorrhoea. The path of solution of this painful problem might be paved out by de-stressing the person through relaxation exercise, yoga and pranayama (the breathing exercises.) Keywords: Primary dysmenorrhoea; psychological stress; yoga. DOI: http://dx.doi.org/10.3126/joim.v32i3.4952 Journal of Institute of Medicine, December, 2010; 32:3 2-4